Analisis Tingkat Keberhasilan Pengelolaan Hutan Kemasyarakatan di Wilayah UPTD KPH Ternate Tidore - Ardanan, Ardanan; Hadun, Ramli; Ryadin, Aisjah Rahmawaty; Kurniawan, Andy; Tjokrodiningrat, Suryati; Rasulu, Hamidin (Universitas Khairun, 2025)
This research analyzes the implementation and development strategy of the Community Forestry (HKm) scheme in the UPTD KPH Ternate Tidore area, with a focus on social, ecological and economic aspects. The aim of this research is to analyze the level of success of community forest management in the UPTD KPH Ternate Tidore area. Research methods include observation, literature study, and questionnaires. To formulate strategies based on strengths, weaknesses, opportunities and threats. Data was analyzed using a stakeholder analysis approach. Stakeholder analysis uses an interest and influence matrix to determine HKm development strategies. The results of the research show that government support, such as simplifying permits, technical assistance, and funding, really supports the sustainability of HKm management. The results of this analysis produce alternative strategies based on government support, optimizing assistant staff, and utilizing forest resources to improve the sustainability of HKm management in KPH areas. Ternate Tidore. produced three alternative strategies, namely: government support for HKm management, optimization of companion workers and utilization of forest resources. This strategy aims to increase the sustainability of forest resources as well as the welfare of surrounding communities.